High‐Entropy Materials for Prospective Biomedical Applications: Challenges and Opportunities - Ling Chang; Haochuan Jing; Chao Liu; Chuantian Qiu; Xiang Ling (Advanced Science)
Abstract With their unique structural characteristics, customizable chemical composition, and adjustable functional characteristics, high‐entropy materials (HEMs) have triggered a wide range of interdisciplinary research, especially in the biomedical field. In this paper, the basic concept, core properties, and preparation methods of HEMs are first summarized, and then the application and development of HEMs in the field of biomedical are briefly described. Subsequently, based on the diverse and comprehensive properties of HEMs and a few reported cases, the possible application scenarios of HEMs in biological fields such as biosensors, antibacterial materials, therapeutics, bioimaging, and tissue engineering are prospectively predicted and discussed. Finally, their potential advantages and major challenges is summarized, which may provide useful guidance and principles for researchers to develop and optimize novel HEMs.